Improving Yields in Rainfed Environments Through Physiological Plant Breeding - Richards, R A; Rebetzke, G J; Herwaarden, A F.Van; Duggan, B L; Condon, A G (Annals of Arid Zone, 2016)
Breeding programs for yield in water-limited environments are plagued by large seasonal variation, low heritabilities and high genotype x environment interactions. A physiological breeding program is described that attempts to identify the principal factors limiting the yield of wheat in Australia. It is notable that the limiting factors identified have more to do with maximizing water use and water use efficiency than with survival under drought. For the characteristics identified, there is substantial genetic variation available in wheat, each having a high heritability so they can be easily screened. They are therefore appropriate for selection in a back crossing program aimed at retaining the desirable quality and disease resistance characteristics already present in wheal') grown in the target region. Identification of highly heritable traits limiting yield and of germplasm containing the desirable expression of the traits also provide valuable parental material and a broader genetic base for empirical breeding programs.